Fatty acid ethanolamine derivatives: metabolism and function - Alharthi, Nahed (2018)
Anandamide is the most recognised member of the N-acylethanolamines, NAEs group. It was the first identified endogenous cannabinoid and TRPV1 agonist as well as acting through PPARs. A wide range of endogenous NAE analogues has been detected in tissues and shown to play a role in many physiological properties. The main aim of this thesis was to investigate the profile of a series of saturated, monounsaturated and polyunsaturated NAEs as substrates for FAAH and to investigate their actions on cannabinoids, TRPV1 and PPARs receptors in vitro.